Building an online platform in support of outcome-focused results-based program management - Förch, Wiebke; Schuetz, Tonya; Abreu, David; Tobon, Hector; Thornton, Philip K. (2015)
• The online platform is uniquely positioned to meet the needs of CCAFS as well as the requirements of CGIAR. • Consensus is needed from the outset about the requirements of such a platform, as the right balance has to be struck between detail and leanness. • We started with a complex, idealistic vision, which was radically simplified through time to promote partner buy-in. The platform was constantly being challenged to be lean and intuitive. • Several testing rounds are needed to get to the right level of minimum requirements and maximum flexibility; at the same time, the conceptual structure of the online platform needs to be robust enough to allow for adjustment. • The conceptualisation of the online platform took the most time and effort; inputs were needed from program managers, project leaders, research and development partners, and monitoring, learning and evaluation experts, to achieve buy-in from an early stage.